Approaches to emergent group differences - CHAN, David (Institutional Knowledge at Singapore Management University, 2019)
This book presents insights on Singapore's economy and society from leading thinkers, based on selected commentaries from Singapore Perspectives conference series co-published by Institute of Policy Studies and World Scientific. Contributed by the who's who of Singapore's government, business and academia circles, they provide diverse viewpoints over economic transformation, globalisation and regionalism, national identity, emerging group differences, ageing, among other important issues.Is the government's growth-at-all-costs policy the most effective for Singapore? Can Singapore advance as a regional hub? Is Singapore a permanent magnet for foreign talent or a transnational revolving door? What is the Singapore Spirit? Are Singaporeans willing to invest their ambition and future in Singapore? What can Singapore do to prepare for an ageing population? This volume explores a range of possible answers to these questions and more.